Merging Top-Down and Bottom-Up Approaches to Fabricate Artificial Photonic Nanomaterials with a Deterministic Electric and Magnetic Response - Dietrich, Kay; Zilk, Matthias; Steglich, Martin; Siefke, Thomas; Huebner, Uwe; Pertsch, Thomas; Rockstuhl, Carsten; Tuennermann, Andreas; Kley, Ernst-Bernhard (Advanced Functional Materials, 2020)
Artificial photonic nanomaterials made from densely packed scatterers are frequently realized either by top-down or bottom-up techniques. While top-down techniques offer unprecedented control over achievable geometries for the scatterers, by trend they suffer from being limited to planar and periodic structures. In contrast, materials fabricated with bottom-up techniques do not suffer from such disadvantages but, unfortunately, they offer only little control on achievable geometries for the scatterers. To overcome these limitations, a nanofabrication strategy is introduced that merges both approaches. A large number of scatterers are fabricated with a tailored optical response by fast character projection electron-beam lithography and are embedded into a membrane. By peeling-off this membrane from the substrate, scrambling, and densifying it, a bulk material comprising densely packed and randomly arranged scatterers is obtained. The fabrication of an isotropic material from these scatterers with a strong electric and magnetic response is demonstrated. The approach of this study unlocks novel opportunities to fabricate nanomaterials with a complex optical response in the bulk but also on top of arbitrarily shaped surfaces.
CRIS-Team Scopus Importer:2023-04-20
Keywords: artificial photonic nanomaterial; cute-wire-pair; electron-beam lithography; optically isotropic material; self-assembly